2018
DOI: 10.15406/jnhfe.2018.08.00282
|View full text |Cite
|
Sign up to set email alerts
|

College student food insecurity and its relationship to fruit and vegetable intake and overweight/obesity at a HBCU

Abstract: USDA-AFSSM, United States department of agriculture adult food security survey module; BMI, body mass index; HBCU, historically black college /university This study assessed the level of food insecurity among students attending a large HBCU; fast food consumption among the food

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Multiple studies have found that African American students are more likely to experience food insecurity (Camelo & Elliott, ; Crutchfield & Maguire, ; Dubick et al, ; Freudenberg et al, ; Goldrick‐Rab et al, ; Martinez et al, ; Morris et al, ; Payne‐Sturges et al, ; Phillips, ; Phillips et al, ). Work around students at historically black colleges and universities also suggests that students at these institutions experience significant food insecurity (Thompson, Gayle, & Castor, ). Forman et al () found that Hispanic students were more likely to experience food insecurity in their study of undergraduates at University of Texas at Austin.…”
Section: Understanding Food Insecurity Among College Studentsmentioning
confidence: 99%
“…Multiple studies have found that African American students are more likely to experience food insecurity (Camelo & Elliott, ; Crutchfield & Maguire, ; Dubick et al, ; Freudenberg et al, ; Goldrick‐Rab et al, ; Martinez et al, ; Morris et al, ; Payne‐Sturges et al, ; Phillips, ; Phillips et al, ). Work around students at historically black colleges and universities also suggests that students at these institutions experience significant food insecurity (Thompson, Gayle, & Castor, ). Forman et al () found that Hispanic students were more likely to experience food insecurity in their study of undergraduates at University of Texas at Austin.…”
Section: Understanding Food Insecurity Among College Studentsmentioning
confidence: 99%